EPISTEMOLOGI 'ULŪM AL QUR`ĀN - Misnawati, Misnawati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
'Ulūm al Qur`ān are discussions related to the Qur'an from various aspects and have a strong relationship with the Qur'an. This knowledge has appeared since the first revelation to Prophet Muhammad (. Meanwhile, the term 'Ulūm al Qur`ān itself was only known in the writings of the scholars 'Ulūm al Qur`ān at the end of the third century AH or early of the fourth century AH.'Ulūm al Qur`ān with various different branches of knowledge did not appear at once. but through a long process of development until it is divided into several periods. And each period has given birth to many books related to this knowledge from many scholars who have emerged. Famous scholars include Imam Badr al Dīn al Zarkasyī who wrote the book Al Burhān fī 'Ulūm al Qur'ān. Then Imam Jalāl al Dīn al Suyūthī wrote the book Al Itqān fī 'Ulūm al Qur`ān. After that Muḫammad `Abd al` Adlīm al Zarqānī wrote the book Manāhil al 'Irfān fī' Ulūm al Qur`ān. These books have become the main reference books for students and researchers of 'ulūm al Qur`ān until now